Physical and Socio-Emotional Development Characteristics of Children with Special Needs - Ketenoglu Kayabasi, Zehra Esra (Nobel Tip Kitabevleri, 2024)
Some of the individuals that make up society continue their lives with diff erent congenital or acquired disabilities due to their developmental characteristics. Individuals are aff ected by disabilities and some disadvantages that may arise due to movement limitation, limb defi ciency, and sensory or spiritual losses that may occur depending on the degree of these disabilities can oft en negatively aff ect their quality of life and social life. In this study, special needs are discussed and concepts such as disability, injury, risk group and disability that lead to special needs are clarifi ed. Th en the disability groups are explained. Disability groups are explained as sub-branches of specifi c learning disability, attention defi cit hyperactivity disorder, autism spectrum disorder, mental disability, physical disability, chronic diseases, language speech disorders, visual impairment and hearing disability. In the last part of the chapter, children with special needs and their socio-emotional characteristics are mentioned.